The Asymmetric Effects of Financial Frictions - Ordoñez, Guillermo (Journal of Political Economy, 2013)
Economic variables move asymmetrically over the business cycle: quickly during crises but slowly during recoveries. I show that this asymmetry is stronger in countries with less developed financial systems and greater financial frictions. Then I explain this fact using a learning model with endogenous information about economic conditions. Financial frictions, which I capture by higher bankruptcy costs, magnify the reaction of lending rates and economic activity to negative shocks and then delay their recovery by restricting information after the crisis. Empirical evidence and a quantitative exploration of the model show that this explanation is consistent with the data.